Barriers to employing e-participation in the Iranian planning system. (September 2021) - Shahab, Sina; Bagheri, Baran; Potts, Ruth
Abstract: e-Participation has been employed by many planning authorities across the world to facilitate the engagement of people in decision-making processes. Previous studies on e-participation have shown that this form of participation can increase the level of flexibility and inclusiveness of public engagements, make government interventions more responsive to citizens' needs, and increase government accountability. While there is a growing use of e-participation in the planning systems of developed countries, its application in developing countries has remained very limited. This paper explores the barriers to employing e-participation in the context of a developing country's planning system, using Iran as a case study. We have conducted interviews with different planning actors, including both public- and private-sector planners, to investigate what they perceive as such barriers. The results of this study show that the primary barriers to e-participation in Iran are attitudes towards participation, the structure and culture of the planning system, and staff capacity to engage the public through e-participation. The paper concludes with a series of recommendations regarding how these barriers can be overcome. Highlights: The use of e-participation in planning is increasingly popular internationally. Little is known about e-participation in developing countries. e-Participation provides opportunities to enhance public participation in planning. There are structural, attitudinal, and infrastructural barriers to use e-participation. Capacity building and allocating required resources can help tackle the barriers.